Role of Fibrinolysis in Sepsis - Gando, Satoshi (Seminars in Thrombosis and Hemostasis, 2013)
Sepsis, defined as infection-induced systemic inflammatory response syndrome, invariably leads to hemostatic abnormalities ranging from insignificant coagulopathy to disseminated intravascular coagulation (DIC). The inflammation-induced activation of coagulation, the downregulation of physiologic anticoagulant pathways, and impairment of fibrinolysis play a pivotal role in the pathogenesis of microvascular fibrin thrombosis and multiple organ dysfunction syndrome (MODS) in DIC associated with sepsis. The balance between tissue plasminogen activator and plasminogen activator inhibitor-1 mainly regulates fibrinolytic activity. Thrombin-activatable fibrinolysis inhibitor and neutrophil elastase also modulate fibrinolysis. Dynamic changes in these molecules are deeply involved in the pathomechanisms of the impairment of fibrinolysis, leading to MODS in DIC associated with sepsis. Evidence indicates that physical entrapment of bacteria by fibrin at the site of infection may limit their capacity to disseminate into nearby tissues, organs, and systemic circulation. Under this circumstance, impairment of fibrinolysis has protective role in the host defense. Given the protective and pathologic potential of fibrinolysis during sepsis, therapeutics that control DIC as a systemic syndrome, while maintaining the host defense at the infectious foci, are required for the protection against both the development of MODS and for the host defense mechanisms.
Keywords: fibrinolysis; disseminated intravascular coagulation (DIC); host defense; sepsis